Stereotactic aspiration of spontaneous intracerebral hematoma: Case series. (2020) - Fahmi, Achmad; Subianto, Heri; Suroto, Nur Setiawan; Utomo, Budi; Sarno, Riyanarto; Turchan, Agus; Bajamal, Abdul Hafid
Highlights: Stereotactic hematoma evacuation can be performed without anticoagulant agent. Stereotactic evacuation of intracerebral hematoma can be adopted in any center. Stereotactic evacuation of intracerebral hematoma is a safe procedure. Stereotactic surgery can minimize brain injury. Abstract: Introduction: Minimally invasive techniques such as stereotactic aspiration of spontaneous intracerebral hematoma (SICH) evacuation can minimize brain tissue damage due to surgery. We share our experience of adopting stereotactic aspiration of SICH in our center without compromising safety. Presentation of cases: Three stereotactic aspiration procedures for SICH immediately after 24 h of onset are reported. All cases showed good results. Level of consciousness of all the patient returned to normal. Two patients could carry out routine activities independently. One patient has left hemiparesis. Discussion: Stereotactic aspiration of SICH has been newly implemented at our center with acceptable results achieved. Patient selection has an important role in determining the choice of technique. The procedures were done without anticoagulant agent. Stereotactic aspiration of SICH is associated with limited brain tissue damage, shorter duration of surgery, reduced length of stay, faster postoperative healing, and better functional improvement. Conclusion: Stereotactic aspiration of SICH is a minimally invasive defined strategy for hematoma evacuation without compromising safety.